1488. Invasive Pulmonary Aspergillosis in Patients with Solid Tumors: Risk Factors and Predictors of Clinical Outcomes. (26th November 2018) - Dandachi, Dima; Dib, Rita Wilson; Fernández-Cruz, Ana; Jiang, Ying; Hachem, Ray Y; Chaftari, Anne-Marie; Raad, Issam
Abstract: Background: The clinical features and management of invasive pulmonary aspergillosis (IPA) in patients with hematologic malignancies are well known. In contrast, IPA is not well described in solid tumor patients. Methods: We retrospectively reviewed all Aspergillus -positive cultures at MD Anderson Cancer Center from March 2004 to September 2017. We included all adult patients with underlying solid tumor and Aspergillus -positive respiratory cultures. The clinical algorithm for IPA diagnosis in critically-ill patients was used to separate colonization from proven or probable infection. We analyzed the association between host factors, clinical findings, and treatment modalities and 12-week overall survival, and response to antifungal therapy. Results: Out of 1, 121 Aspergillus -positive cultures, 669 cases did not meet the inclusion criteria and 351 were classified as colonization. We included 101 patients with IPA and solid tumor; 10% proven and 90% probable IPA. The median age was 63 years. The most common underlying solid tumor was lung cancer (51%), 76% of the patients had an underlying lung disease, 47% had received radiation therapy to the chest, and 33% had chronic obstructive pulmonary disease. Neutropenia and diabetes were not common risk factors. Most patients presented with respiratory symptoms (81%). A. fumigatus was the most common type isolated (69%). Most common chest imaging findings were nodular (41%) and cavitary lesions (14%); 70% of the patients were treated with voriconazole monotherapy. Independent risk factors for 12-week mortality were receiving steroids within 30 days of IPA diagnosis (hazard ratio 2.2, 95% CI, 1.1–4.6; P = 0.03) and radiation therapy to the chest (hazard ratio 2.6, 95% CI, 1.2–5.5; P = 0.01). In multivariate analysis, a positive calcofluor fungal stain was associated with lower odds of a successful outcome (odds ratio 0.2; 95% CI, 0.05–0.75; P = 0.02) whereas treatment with voriconazole was associated with higher odds (odds ratio 10.1; 95% CI, 2.1–48.5; P < 0.01). Conclusion: IPA should be considered in solid tumor patients, particularly those with underlying lung disease. Radiation therapy to the chest, steroid intake, and positive fungal stain were associated with poor outcomes, while voriconazole therapy was associated with improved outcomes. Disclosures: I. Raad, The University of Texas MD Anderson Cancer Center: Shareholder, Licensing agreement or royalty. The Unversity of Texas MD Anderson Cancer Center: Shareholder, Dr. Raad is a co-inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed to Novel Anti-Infective Technologies LLC, in which UTMDACC and Licensing agreement or royalty.